A Literary Review of Trunapanchamula w.s.r to Role in Stanya Janana (AYUSHDHARA, 2022)
Breastfeeding is a hormonal, emotional physical and dietary phenomenon certain to be affected by every component. As Milk is a completely unique and whole nutritive supply for the mammal neonate, additionally imparting immune safety and developmental signals, it is the best way to care for new born. Besides creating the overwhelming bonding, it is also the perfect nourishment for them. In Ayurvedic texts, formation of Stanya (Breast milk), causes of Stanya pravriti (or milk ejection), Dhatri (wet-nurse), Dhatri-pariksha (examination of wet-nurse), Stanapan-vidhi (Breast feeding), Stanyasampat (merits of Breasts) etc. are described by different Acharyas Since try should be made to prevent it with right anticipation via multidimensional approach comprising of physical methods, provisions of nutritious lactogenic eating regimen and use of herbal galactagogues cited thoroughly in Ayurvedic literature. Synthetic Galactagogues cited in cutting-edge sciences pose a more chance of detrimental health dangers at the same time as Ayurveda manage protocol addresses internal balances and outdoor influences contributing to problem. Charaka also described Stanyajanana Mahakasaya likewise Susruta Vagabhatta described Gana in where Trunapanchamula is included in that. So, this review gives an integrated overview of the physiology of lactation with particular focus on physiology of milk production and secretion in respect to Ayurvedic and modern concept with special reference to Trunapanchamula.